Optimalisasi Peran Lembaga Zakat Dalam Mewujudkan Keadilan Sosial-Ekonomi - Atmo Prawiro; Ahmad Khoirul Fata (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2020)
This paper seeks to answer important questions on the role of zakat institutions in the distribution of social and economical justice in society. This paper is motivated by the concept that zakat is a sharing economy or gift economy that is believed to be able to contribute to increasing the prosperity and welfare of society. But in the Indonesian context, zakat has not been able to playfully that role. At this point zakat management institutions (amil) should be highlighted as zakat fund managers. To optimize the zakat funds, the amil zakat must pay attention to several things: zakat management must be done professionally and clearly, zakat funds must be used as entrepreneurial capital, as eternal funds, sustainable and sustainable capital, zakat institutions must have clear targets and planned, and finally Amil must be willing to collaborate and cooperate between them.